The Healthy Indonesia Program and Family Role In Dealing with Covid-19 In Indonesia - Ismunandar, Ismunandar; Hafid, Fahmi; Taqwin, Taqwin; Zainul, Zainul; Junaidi, Junaidi; Nasrul, Nasrul (Poltekkes Kemenkes Palu, 2021)
The Healthy Indonesia Program with a Family Approach (PIS-PK) aims to improve the quality of life of Indonesian citizens from the smallest unit of society, namely the family. This program is the family's main capital in dealing with the COVID-19 pandemic. The purpose of this study was to assess the potential of the Healthy Indonesia program and the role of families in dealing with Covid-19 in Indonesia. Literature review was conducted during 27 July 2021 to 07 August 2021, and literature search used Publish or Perish software for the time period of 2020-2021. Search keywords include: Coronavirus, Vaccines, Covid-19, Healthy Indonesia Program, Family Planning, delivery in health facilities, complete basic immunization, Exclusive Breastfeeding, growth monitoring, pulmonary tuberculosis, hypertension, mental disorders, smoking, National Health Insurance, access to clean water facilities and healthy latrines. Study findings showed that family planning services, delivery in health facilities, complete basic immunization, and growth monitoring could still be implemented by families in Indonesia. Likewise, the treatment of tuberculosis, hypertension, mental disorders is carried out on a limited basis. The behavior of exclusive breastfeeding, no smoking family members, families which have become members of the National Health Insurance and families which have access to clean water facilities are family capital in dealing with the covid-19 pandemic. In conclusion, the more complete the status of a healthy family based on 12 indicators, the more resilient each family will be in dealing the covid-19 pandemic.